SAHA TÜRKÇESİNDE FARKLI BİR KİP “-llhl(k)” - KİRİŞÇİOĞLU, Fatih (Acta Mongolica, 2005)
In this research,the areas where the -Ilhl(k), the positive mood in Sakha(Yakut) turkish,is used,were studied and the views of the researchers on the etimology of the suffix were reported.In view ofthe findings, it was concluded that the etimology of the suffix might have been derived from the suffix -slk or the suffixal in ancient Turkish.